Comfort conditions for hypermarket workers: from experimental data to best practices - Martellotta, Francesco; Della Crociata, Sabrina; Simone, Antonio; Calderoni, Leonardo; d'Alba, Michele; Cervellati, Massimo; Papapietro, Nunzio (La Medicina del Lavoro, 2014)
Background: Thermal, acoustic and visual comfort conditions for hypermarket workers have never been investigated with scientific methods. Objectives: taking advantage of a case study, with characteristics capable of generalizing the results, analytically measure the actual comfort conditions to which workers are exposed and point out possible ameliorative proposals. Methods: Carry out a detailed survey based on instrumental measurements combined with subjective questionnaires to assess the indoor environment. Results: Even though the analysis pointed out no significant risk conditions, several smaller problems appeared in terms of local discomfort (such as cold limbs, higher sound level exposure, limited glare phenomena) for cashier workers. The origin of these problems appeared to be the pivotal position of the cash registers. Conclusions: Taking into account observed phenomena and their causes a list of “best practices” has been defined hoping that their adoption could further limit any impact on workers comfort conditions.